Aerospace Materials What will builders use?.
The volume of composites and titanium alloys used in the aerospace field grows daily, but aluminum won't be going away. Producers of aluminum expect the volume of the metal used in the aerospace industry to grow by more than 6% annually from 2010 to 2013.
Keywords: Aerospace Materials